Development of Team-Based Project Biochemistry Practicum Manual to Create Practicum Product - Diah Kartika Sari; Made Sukaryawan; Rodi Edi; Eka Ad'hiya; Sanjaya; Andi Suherman; Dea Dwi Andini; Yara Dwinadia (Postgraduate, University of Mataram, 2024)
Team-based learning is learning that is imposed on students to improve students' critical thinking, problem solving, solution finding, and communication skills. This learning is also useful for lecturers as teaching staff to improve higher abilities and skills. Researchers will combine practicum instructions with a team-based learning model. Team-based project practicum instructions will be able to make students together do practicum utilizing the surrounding environment to produce practicum products. This research is a research development with ADDIE development model and Tessmer formative evaluation. The research stages consist of self evaluation, expert reviews, one to one, small group. The innovation and originality of this research is the valid and practical team-based project practicum instructions used in Biochemistry practicum lectures. The results of the research were tested and used in Biochemistry team-based project practicum lectures. The results of laboratory development validation show the Aiken coefficient of 0.86 for material experts and 0.90 for design experts. The results of the implementation show the practicality of 96.45%. It can be concluded that the biochemistry lab instructions on team based project developed in the Biochemistry practicum is valid and practical.